Inspiring Writing in Primary Schools - Chamberlain, Liz (SAGE Publications, 2018)
Through teaching fabulous lessons teachers can help children to discover stories, create worlds, record events, mould characters and inspire each other as writers. This book provides the guidance and examples to help achieve this.